Poetry and mysticism in Islam : (Cambridge University Press, 1994)
Maulana Jalal al-Din Rumi was one of the greatest poets and mystics of the Islamic world. He was born in Balkh (Korasan) in 1207 AD and died in Konya (Turkey) in 1273 AD. This book is an examination of his spiritual and literary heritage. As Annemarie Schimmel, the recipient of the Eleventh Giorgio Della Vida Award in Islamic Studies, has written, no other mystic and poet from the Islamic world is as well known in the West as Rumi, and she, more than any Western scholar, is his most celebrated and eloquent interpreter. The scholars whom Professor Schimmel has invited to share in her tribute have all added new dimensions to an understanding of Rumi and to his impact on the Islamic world.